Vizualizacijska metoda merjenja deformacije lopatic aksialnih ventilatorjev - Eberlinc, Matjaž (Ventil (Ljubljana), 2007)
Axial-flow fan blades deform during operation due to the various forces that act on them. The steady-state deformation and fluctuation of the blade peak, i.e., the vertex around the poise position, allow us to evaluate the volume ofload, where the blade is fixed on the rotor, and assess the influence of thedeformation on the aerodynamic characteristics of the axial-flow fan. In the paper we present the methodology for measuring the deformation of the axial-flow fan blade, which is supported by a computer-based visualization. The experiment was carried out on an axial-flow fan, with both basic and modified constructions, where the blade is fixed to the rotor. Measurements were carried out on the measuring station at the Faculty of Mechanical Engineering, University of Ljubljana, where using a high-speed camera we obtained digital pictures at selected time intervals. The deformations of the axial-flow fan blade were measured at the optimal working point for the axial-flow fan with the basic and modified constructions. On the blade vertex,we evaluated the deviation of the measuring point, in terms of the reference point that is on the fan casing. We have written software in Matlab to recognize the measuring points and to calculate the blade deformation on the vertex of the axial fan blade. With the help of the developed visualization method, we compared results that we got from the axial-flow fan with the basic and modified constructions. The experimental method used in this paper can easily and reliable detect the deformation of the axial-flow fan blade.
Keywords: aksialni ventilatorji; deformacije; lopatice; vizualizacija